2021
DOI: 10.1038/s41598-020-79500-x
|View full text |Cite
|
Sign up to set email alerts
|

5G as a wireless power grid

Abstract: Abstract5G has been designed for blazing fast and low-latency communications. To do so, mm-wave frequencies were adopted and allowed unprecedently high radiated power densities by the FCC. Unknowingly, the architects of 5G have, thereby, created a wireless power grid capable of powering devices at ranges far exceeding the capabilities of any existing technologies. However, this potential could only be realized if a fundamental trade-off in wireless energy harvesting could be circumvented. Here, we propose a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…2) Conformable and low antenna profile for improved integration in clothing and on thinner substrates [21]. 3) Broad bandwidth, to enable the antennas to be used in the full 5G spectrum [12], [17]. While several theoretical and practical studies have shown the benefits of mmWave WPT [4], [9], [12], the performance of a mmWave-powered network based on a real antenna, meeting the above criteria, remains unclear.…”
Section: A Mmwave Antenna and System Requirements For Wptmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Conformable and low antenna profile for improved integration in clothing and on thinner substrates [21]. 3) Broad bandwidth, to enable the antennas to be used in the full 5G spectrum [12], [17]. While several theoretical and practical studies have shown the benefits of mmWave WPT [4], [9], [12], the performance of a mmWave-powered network based on a real antenna, meeting the above criteria, remains unclear.…”
Section: A Mmwave Antenna and System Requirements For Wptmentioning
confidence: 99%
“…3) Broad bandwidth, to enable the antennas to be used in the full 5G spectrum [12], [17]. While several theoretical and practical studies have shown the benefits of mmWave WPT [4], [9], [12], the performance of a mmWave-powered network based on a real antenna, meeting the above criteria, remains unclear. To explain, the benefits of mmWave WPT compared to its UHF counterpart need to be evaluated.…”
Section: A Mmwave Antenna and System Requirements For Wptmentioning
confidence: 99%
See 1 more Smart Citation
“…Such solutions are impractical and inefficient, especially with the deployment of billions of IoT devices in arbitrary locations and over a large city. Eid et al [99] proposed a system capable of harvesting the 5G/mm-wave energy from all directions, thereby breaking the aforementioned tradeoff of simultaneous high gain antennas and wide angular coverage. To realize this, the authors incorporated a fully printed planar Rotman lens in their rectenna design, as an intermediate element between the antenna arrays and the rectifiers.…”
Section: Flexible 5g/mm-wave Devices and Sensors For Energy Harvesting And Backscatter Communicationsmentioning
confidence: 99%
“…The Rotman lens is a unique type of passive BFNs that combines all the power received on its antenna ports, on one side, and focuses it towards the beam port(s) associated with the direction of arrival of the signal. Depending on the intended use, rectifiers such as in [54], [55] can be placed at the beam ports to collect the RF power and convert it to DC, or switches such as in [56] can be connected to modulate the signal and reflect it back for communication purposes. Unlike the Van Atta structure that divides the power among its lines and is, therefore, ill-suited for optimal harvesting performance, the Rotman lens-offering RF combination-can enable the operation of fully-passive RFID tags at longer turn-on ranges, if rectifiers are connected to the beam ports to power the tag.…”
Section: ) Rotman Lens Retrodirective Architecture For Fully-passive Mmidmentioning
confidence: 99%